2017
DOI: 10.1002/slct.201601725
|View full text |Cite
|
Sign up to set email alerts
|

A Quaternary Ammonium Salt Promoted Regioselective Iodination of Terminal Alkynes: A Convenient Access to 1‐Iodoalkynes in Aqueous Media

Abstract: A new protocol for the synthesis of 1‐iodoalkynes from terminal alkynes under metal‐free conditions in aqueous media via quaternary ammonium iodide and oxone mediated oxidative iodination has been developed. Simple reaction conditions, low cost and commercial availability of reagents and the use of readily available, non‐toxic and universal solvent i. e., water as a reaction media makes this approach as an eco‐friendly and economically viable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…are available to realize 1-haloalkynes . Recently, Srujana et al developed a new green synthetic protocol for 1-iodoalkynes ( 44 ) starting from terminal alkynes 43 . The method worked under metal-free, aqueous conditions catalyzed by tetrabutyl ammonium iodide and oxone (Scheme ) Simple reaction conditions, use of low-cost commercial reagents as well as readily available, nontoxic, and universal solvent (water) makes this approach eco-friendly and economically viable.…”
Section: Synthesismentioning
confidence: 99%
“…are available to realize 1-haloalkynes . Recently, Srujana et al developed a new green synthetic protocol for 1-iodoalkynes ( 44 ) starting from terminal alkynes 43 . The method worked under metal-free, aqueous conditions catalyzed by tetrabutyl ammonium iodide and oxone (Scheme ) Simple reaction conditions, use of low-cost commercial reagents as well as readily available, nontoxic, and universal solvent (water) makes this approach eco-friendly and economically viable.…”
Section: Synthesismentioning
confidence: 99%
“…Conventional approaches for the synthesis of 1-iodoalkyne compounds include the direct oxidative iodination of terminal alkyne with iodinating reagents, most frequently molecular iodine or hypervalent iodonium salts, to afford corresponding 1-iodoacetylenes . With quaternary ammonium iodide and oxone-mediated oxidative iodination, high yields of alkyne iodination were also achieved …”
mentioning
confidence: 99%
“…35 With quaternary ammonium iodide and oxone-mediated oxidative iodination, high yields of alkyne iodination were also achieved. 36 This potentially useful on-DNA iodination was explored, despite the known sensitivity of DNA to oxidization 14 and iodination, 37 in the hopes that a judicious choice of reaction conditions could circumvent those challenges. After evaluating commonly utilized off-DNA iodinating approaches, we concluded that the copper iodide-promoted iodination with N-iodosuccinimide (NIS) was feasible to execute on-DNA.…”
mentioning
confidence: 99%